Estimating Carbon Sequestration Rates and Total Carbon Stockpile in Degraded and Non-Degraded Sites of Oak and Pine Forest of Kumaun Central Himalaya - Jina, B. S.; Sah, Pankaj; Bhatt, M. D.; Rawat, Y. S. (Ecoprint: An International Journal of Ecology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> We calculated the rates at which CO2 is being sequestered in two different forest types of Himalaya. For our comparative study we took the degraded and non-degraded sites of pine and oak forests in Kumaun Central Himalaya. The Van Panchayats (VPs) or Community Forests are managing the nondegraded forest sites for centuries, and from this research we have come to know that the sequestration of CO2 in these non-degraded forests is significantly greater than the degraded forests. The paper recommends the significance of community forests in both Uttarakhand and the world, and advocates that if we want to fight against global warming, we must encourage the community forests and that the people living in severe poverty in these forest areas who become the unsung heroes in the war against global warming, must be paid in lieu of saving their forests, which ultimately become the sink for increased CO2 worldwide. This business or ‘carbon trading' will indeed evolve as the panacea against the war against global warming. Key words: Carbon sequestration, community forests, Van Panchayats, green house gases, global warming, carbon trading. doi: 10.3126/eco.v15i0.1946 ECOPRINT 15: 75-81, 2008